Pajak Kini, Pajak Tangguhan, Aset Pajak Tangguhan, Liabilitas Pajak Tangguhan Terhadap Manajemen Laba - Marista Winanti Sutadipraja; Sri Setia Ningsih; Mardiana Mardiana (Journal of Applied Accounting and Taxation, 2020)
The purpose of this study was to examine whether there is an effect of current tax expense, deferred tax, deferred tax assets, and deferred tax liability on earnings management actions in consumer goods companies listed on the Indonesia Stock Exchange (IDX). This study's sample consisted of 27 consumer goods industries listed on the Indonesia Stock Exchange in 2013-2017 using the purposive sampling method. Hypothesis testing in this study using the t-test. Earnings management is proxied by discretionary accruals using the Modified Jones Model. The type of data used is secondary data. Data analysis used OLS (regression equation analysis ordinary least square). The results show that the current tax has a significant effect on earnings management variables. The deferred tax affects earnings management, deferred tax assets affect earnings management, and deferred tax liabilities have no effect on earnings management. Research limitations The sample of companies used is considered less representative of the population because only manufacturing companies are used consumer goods. The research period in measuring earnings management variables is proxied by discretionary accruals for only five consecutive years, according to Jones (1991). profit can be seen if the research period is carried out for eight years. In this study, it is suggested that the research period used can be added, and the sample used can be extended to other company sectors and other measures of earnings management by using proxies.